BUILDING INSURANCE BRAND IMAGE IN THE SME SECTOR IN POLAND – AN EMPIRICAL STUDY - Aneta, ONISZCZUK-JASTRZABEK; Joanna, BEDNARZ; Tomasz, CZUBA; Piotr, CZECHOWSKI Oskar (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 20 (2018): Annales Universitatis Apulensis Series Oeconomica, 2018)
The source of the distinctive offer are: product design, its features, technology of production, consumer services and a well-known brand appreciated by consumers. Branded products are perceived by consumers as remarkable, that are not able to be substituted by the goods offered by competitors. The brand and its image provide the customer with an emotional or symbolic benefits that are essential in building strong relations between a company and its clients. The similar mechanism is observed on the insurance market. PZU SA has been the best known Polish insurance company indicated by SMEs for the period 2012-2017. It is worth to mention that its spontaneous brand awareness is over 90%. For these reasons PZU SA can be perceived as a good example of the business model for other insurance companies. The aim of this paper is to identify the most important factors that affect the image of insurance companies present on the Polish market. Basing on the association tests the authors also tried to discover the specific image of each company. The method of direct interview was used to collect data from respondents representing the SME sector (survey method: direct interview (PAPI)). For each of the groups, the sampled group is representative. To present results independently from the number of employees shown in the report as SMEs IN TOTAL (weighted data in total), a system of weightings was developed to allow obtaining results for the entire market. The sampling was done randomly using a list of companies drawn up by the Main Statistical Office (GUS). The algorithm for selecting companies to represent the SME sector was developed by a specialist from Qualifact company. Companies were chosen with the use of systematic draw technique. Targeting the examined population according to the section (production, construction, trade, hotels / restaurants, transport, financial intermediation, real estate, education, others) and province, guaranteed appropriate proportion of the number of companies representing different economic sectors.